Reaction Pathways of Alkoxyl Radicals. The Role of Solvent Effects on C–C Bond Fragmentation and Hydrogen Atom Transfer Reactions - Salamone, Michela; Bietti, Massimo (Synlett, 2014)
This account describes the results of our recent mechanistic studies on unimolecular C–C bond fragmentation (β-scission and O-neophyl rearrangement) and bimolecular hydrogen atom transfer (HAT) reactions of alkoxyl radicals. Particular attention is devoted to the study of solvent effects on these reactions by means of time-resolved techniques such as laser flash photolysis. Information is provided on the effect of ring substituents and of the solvent on the spectral properties of arylcarbinyloxyl radicals and on their reactivity in β-scission and O-neophyl rearrangement reactions, showing that a change in solvent can influence the fragmentation reactivity and selectivity. Detailed information has also been obtained on the role of the substrate structure and of the solvent on HAT reactions involving the cumyloxyl radical, showing the importance of solvent hydrogen bond interactions with the substrate and/or the radical on these processes, and providing a general mechanistic description of the kinetic solvent effects observed in HAT reactions from C–H bonds, as well as expanding on the previously available description for HAT from phenolic O–H bonds. The possible application of these findings to synthetically useful C–H functionalization procedures is discussed.1 Introduction2 C–C β-Scission Reactions3 O-Neophyl Rearrangement4 Hydrogen Atom Transfer (HAT) Reactions5 Concluding Remarks
Keywords: radical reactions; alkoxyl radicals; solvent effects; hydrogen atom transfer; β-cleavage; O-neophyl rearrangement